Detection of Neoparamoeba perurans by duplex quantitative Taqman real‐time PCR in formalin‐fixed, paraffin‐embedded Atlantic salmonid gill tissues - E Fringuelli; A W Gordon; H Rodger; M D Welsh; D A Graham (Journal of Fish Diseases, 2012)
The development and the application of a quantitative duplex real‐time PCR for the detection of Neoparamoeba perurans and the elongation factor α 1 gene (ELF) of Atlantic salmon, Salmo salar L., and rainbow trout, Oncorhynchus mykiss (Walbaum), are described. A set of primers and probe was designed to amplify a 139‐bp fragment specific to the N. perurans 18S rRNA gene. The test was shown to be very sensitive, being able to detect as little as 13.4 DNA copies per μL corresponding to 0.15 fg of template DNA. In addition, the reaction that detected N. perurans was found to have a high degree of repeatability and reproducibility, to have a linear dynamic range ( R 2 = 0.999) extending over 5 log 10 dilutions and to have a high efficiency (104%). The assay was applied to DNA samples extracted from 48 formalin‐fixed, paraffin‐embedded (FFPE) salmon gill tissues showing varying degrees of gill histopathology and amoebic gill disease (AGD)‐type histopathology ranging from absent to severe (each scored 0–3). Neoparamoeba perurans DNA was detected in all the blocks where AGD‐type histopathology was diagnosed microscopically and in 43.6% of the blocks showing signs of gill pathology. The association between parasitic load and gill histopathology and AGD‐type histopathology severity was also investigated. This study also describes the development and the application of a second real‐time PCR for the generic detection of Neoparamoeba spp ., Page, 1987. A set of primers and probe conserved among the Neoparamoeba spp. was designed to amplify a 150‐bp fragment within the 18S rRNA gene. Applied to N. perurans‐ negative gill tissues, the method was used to exclude the presence of other Neoparamoeba spp. in those blocks where gill pathology was observed microscopically.